Clinicopathologic Analysis of Angioimmunoblastic T-cell Lymphoma With or Without RHOA G17V Mutation Using Formalin-fixed Paraffin-embedded Sections. (August 2016) - Nagao, Ryoko; Kikuti, Yara Yukie; Carreras, Joaquim; Kikuchi, Tomoki; Miyaoka, Masashi; Matsushita, Hiromichi; Kojima, Minoru; Ando, Kiyoshi; Sakata-Yanagimoto, Mamiko; Chiba, Shigeru; Nakamura, Naoya
Abstract : Angioimmunoblastic T-cell lymphoma (AITL) is an infrequent subtype of peripheral T-cell lymphoma derived from follicular helper T cells. Recently, a somatic G17V RHOA gene mutation has been reported. In this article, we examined the RHOA G17V mutation in 18 cases of AITL by 3 different techniques of Sanger sequencing, fully automated SNP genotyping, and deep sequencing, using routine diagnostic formalin-fixed paraffin-embedded tissue. The RHOA G17V mutation was detected in 10 cases (56%). Among the 10 mutated cases, 8 cases were detected by all 3 methods. The status of RHOA mutation was subsequently compared with the clinicopathologic characteristics of AITL. RHOA -mutated AITL (10 cases) was clinically characterized by high serum IL-2R and a poor ECOG performance status. By immunohistochemistry, expression of CD10, PD-1, CXCL13, and CCR4 and a wide distribution of CD21(+) follicular dendritic cells were observed in RHOA -mutated cases. Among these, CCR4 expression and the CD21(+) network in RHOA -mutated AITL cases were more extensive than in the RHOA mutation-negative AITL cases ( P <0.05). Thus, RHOA -mutated AITL cases are more characteristic of follicular helper T cells, and the presence of such a mutation is an important marker for AITL.